Plasmodium vivax Infection in Multiple Family Members in Texas, USA - Roukaya Al Hammoud; James R. Murphy; Michael L. Chang (Case Reports in Infectious Diseases)
We report a cluster of 6 pediatric residents of Houston, Texas, USA, who presented with Plasmodium vivax infection within an eight-week period. All had immigrated to the United States from Afghanistan within the previous year. The clustering raises the possibilities of local mosquito vectored infection and/or synchronous relapses. Molecular typing and local mosquito testing are crucial in delineating the source of similar clusters in nonendemic regions. Single-dose hypnozoite eradication treatment may be considered in emigrating children to malaria nonendemic countries.